Estudo sobre a emancipação no ajuste profissional de ex-cortadores de cana-de-açúcar em usinas sucroalcooleiras no noroeste do Estado do Paraná - Silva, Patrícia Rodrigues da (2010)
The world of work running through changes that impact directly on the subjectivity of workers, changing the way in which they are embedded in social and organizational structures. The concept of career is now seen as a responsibility of individuals, that to adjust in the organizational structure, they begin to develop competencies and skills that meet the responsibilities of his new role, beyond the needs and expectations of the organization.These changes in the working world also impacted the sugar cane industry and its workers, so we chose to study in this thesis professional adjustment ex-cutters cane sugar for administrative functions, operational-level, in sugarcane mills in the Northwest region of the state Parana, from the perspective of human emancipation. The relevance of this work lies in providing the intersection between the humanities and social sciences, through the themes developed, but also discuss about the changes engendered in the subjectivities of workers who experienced the professional adjustment in sugarcane mills, which also raised a new role of these workers in the social hierarchy. From this perspective of changing of the world of work, it became important to describe the perceptions of individuals about the professional setting experienced by ex-cutters cane sugar, in search of understanding the phenomenon being studied, ie, the professional adjustment . The research is descriptive and qualitative in nature. The cutoff time is sectional with a longitudinal perspective, because the data are collected at a point in time, but rescues the transformations of the studied phenomenon. The research was used for primary and secondary data. The primary data collection was through semi-structured interview with the ex-cutters cane sugar and their HR managers. Secondary data were collected in order to raise the historic sugar cane and work cutting sugar cane. The interpretation of the data was collected through content analysis. Thus, the research conducted in this thesis allowed through the participants' reports of externalizing their feelings about the professional setting experienced by the former sugar cane cutters, revealing their perceptions about the adjustment, which led these workers to function fully and brutal for new functions that were more intellectual. From the interpretations made, it was concluded that there is no evidence of emancipation of the workers after adjusting professional experienced by them, was not identified as a dialogical action and mutual understanding. It was observed that the workers were absorbed into the ideology of sugarcane mills and have been co-opted.